Assessing Quality and Safety of an Advanced Practice Provider-Led Active Surveillance Clinic for Men with Prostate Cancer. Issue 5 (29th September 2021) - Clements, Matthew B.; Lin, Xin; Gmelich, Caroline; Vertosick, Emily A.; Vickers, Andrew J.; Manasia, Michael K.; Wolchasty, Natalie C.; Scardino, Peter T.; Eastham, James A.; Laudone, Vincent P.; Touijer, Karim A.; Ehdaie, Behfar
Abstract: Introduction: We implemented an advanced practice provider (APP)-led clinic to aid in managing the growing population of men on active surveillance (AS) for prostate cancer. Our objective was to evaluate the quality and safety of an established APP-led AS clinic by comparing outcomes with urologist-led biopsies, defined in terms of adherence to scheduled visits and biopsy complications. Methods: We performed a retrospective review of 2, 341 consecutive patients treated in an AS clinic at a high-volume referral center between 2000 and 2019. We examined the rate of no-show or same-day cancellation of visits for APPs versus urologists and compared the risk of biopsy complications between these providers. Generalized estimating equations were used to account for repeated visits and biopsies. Results: There were significantly more no-shows at APP visits (OR 1.40, 95% CI 1.16–1.70; p <0.001); however, this only amounted to 1 no-show every 41 visits. There was no evidence of increased biopsy complications with APPs (OR 0.37, 95% CI 0.05–2.49; p=0.3). Patients were not prospectively assigned to APP or urologist management; therefore, unmeasured patient differences could bias our results. Conclusions: We demonstrated that in an established APP-led AS clinic at a high-volume center, APPs achieved acceptable patient adherence to scheduled visits and biopsy complications. Because patients were not continuously managed by one type of provider, further prospective studies are needed to establish equivalent pathological outcomes in APP-managed AS.